Efficient [(NHC)Au(NTf2)]-catalyzed hydrohydrazidation of terminal and internal alkynes - Heidrich, Maximillian; Plenio, Herbert (Beilstein Journal of Organic Chemistry, 2020)
The efficient hydrohydrazidation of terminal (6a–r, 18 examples, 0.1–0.2 mol % [(NHC)Au(NTf2)], T = 60 °C) and internal alkynes (7a–j, 10 examples, 0.2–0.5 mol % [(NHC)Au(NTf2)], T = 60–80 °C) utilizing a complex with a sterically demanding bispentiptycenyl-substituted NHC ligand and the benign reaction solvent anisole, is reported.
Keywords: alkyne; gold; homogeneous catalysis; hydrohydrazidation; NHC ligand